Switzerland Citizens’ Personal, Political, Economic and Social Rights and Freedoms - O. N. Litvinyuk (Московский журнал международного права, 2010)
The article includes the Swiss experience of human and citizen rights and freedoms development. Full number of topics on personality status as well as personal, political and social rights in Switzerland has been considered, including the right to life, freedom and inviolability of personality and private life, freedom of press, conscience and religion, freedom of unions and associations, demonstrations and assembly, minimal existence, strikes and one of the main rights of the country – the right to speak native language.